Regulation of Immune Responses and Chronic Inflammation by Fibroblast-Like Synoviocytes - Yoshitomi, Hiroyuki (Frontiers in Immunology, 2019)
Synovial tissue is a membranous nonimmune organ lining joint cavities where it supports local immune responses and contributes directly and indirectly to joint destruction in chronic inflammatory diseases such as rheumatoid arthritis (RA). Fibroblast-like synoviocytes (FLSs), the dominant nonimmune cells of synovial tissues, contribute mainly to joint destruction via multiple mechanisms. Synovial hyperplasia involving FLSs provides the space for inflammation and immune responses, where FLSs can exert their RA effector functions, respond to endogenous ligands, and modulate immune responses. Here, we describe new findings and review the mechanisms underlying the regulation of immune reactions by non-immune FLSs and their roles in inflammatory diseases, mainly in RA.